Load characterization and revenue metering under non-sinusoidal and asymmetrical operation - Tenti, Paolo; Costabeber, Alessando; Marafão, Fernando P.; Parades, Helmo K.M. (IEEE, 2013)
This paper proposes an approach to load characterization and revenue metering, which accounts for the influence of supply deterioration and line impedance. It makes use of the Conservative Power Theory and aims at characterizing the load from the measurements done at the point of common coupling. Despite the inherent limitations of a single-point measurement, the proposed methodology enables evaluation of power terms, which clarify the effects of reactivity, asymmetry and distortion, and attempts to depurate the power consumption accounted to the load from those terms deriving from supply nonidealities.